RETRACTED: THE IMPLEMENTATION OF JOBSHEET-BASED STUDENT TEAMS ACHIEVEMENT DIVISION LEARNING MODEL TO IMPROVE STUDENTS LEARNING OUTCOMES - Permana, Kadek Dodi; Sunarya, I Made Gede; Santyadiputra, Gede Saindra (Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
RETRACTED Following a rigorous, carefully concerns and considered review of the article published in Jurnal Pendidikan Teknologi dan Kejuruan entitled "The Implementation of Jobsheet-Based Student Teams Achievement Division Learning Model to Improve Students Learning Outcomes", Vol 23, No 2, pp. 152-162, October 2016 DOI: http://dx.doi.org/10.21831/jptk.v23i2.13183 This paper has been found to be in violation of the Jurnal Pendidikan Teknologi dan Kejuruan Publication principles and has been retracted. The article contained redundant material, the editor investigated and found that the paper published in Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika (KARMAPATI) ISSN: 2252-9063, Vol. 4, No. 4, 2015. The document and its content has been removed from Jurnal Pendidikan Teknologi dan Kejuruan, and reasonable effort should be made to remove all references to this article.